"Grateful" Children and "Humanitarian" Marines: Georgette "Dickey" Chapelle's Vietnam Photography, 1962. (22nd July 2022) - Vesma, Georgia
Abstract: This article explores how one female photographer, Georgette 'Dickey' Chapelle (1918–1965), used children's emotions as visual and rhetorical justification for early 'advisory' actions in Vietnam by the United States, situating the presence of U.S. Marines in Vietnam as 'humanitarian'. Children are a common subject for 'humanitarian photography', mobilising an emotional response and justifying certain actions as humanitarian (Fehrenbach and Rodogno, Humanitarian Photography: A History . Cambridge University Press, 2015). War photography studies have explored the creation of a 'humanitarian soldier' to justify colonising conflicts in the twenty-first century (Parry, Media, Culture and Society 33 (8): 1185–1201, 2011; Kotilainen, "Humanitarian Soldiers, Colonialised Others and Invisible Enemies-Visual Strategic Communication Narratives of the Afghan War." FIIA Working Paper, 2011). This paper brings these ideas to a case study from the Vietnam War era, emphasising the role of emotional constructions in the production of such 'humanitarian' interpretations of military activity. In her article for National Geographic, "Helicopter War in Viet Nam, " Chapelle focused on interactions between uniformed American men and Vietnamese children, whom she portrayed as grateful recipients of airlifts, clothing and medical treatment. Chapelle used children to symbolise South Vietnam, reflecting political discourses in the United States that presented Vietnam as a 'childlike' nation in need of 'rescue'. While many photographs of children from the Vietnam War era were used as evidence of the moral indefensibility of the conflict, this paper argues that Chapelle's photographs from the Mekong Delta in 1962 portray Vietnam as 'childlike' to justify American intervention in Vietnam as 'humanitarian'.